SEXUAL ABUSE AND RISK OF CHRONIC ILLNESS: A LITERATURE REVIEW - Sujana, Treesia (Journal of Maternity Care and Reproductive Health, 2024)
Sexual violence is a traumatic event that often has a long-term impact on physical and mental condition. The existing research primarily focuses on the prevalence and general impacts of sexual violence however, there appears to be a paucity of research investigating the specific long-term effects of sexual violence on women. The aim of this literature review is to described the relation between sexual abuse and the risk of Chronic Illness. This study employs a thematic literature review methodology utilizing the Onwegbuzie & Frels Seven Step model, which is particularly suitable for qualitative research literature reviews; however, it is sufficiently flexible to be applied to other research paradigms. In this study, literature was selected incorporating both qualitative and quantitative studies. Journal articles were identified and selected through the EBSCO and SCOPUS web bases. Twenty papers were then selected according to the following criteria: study conducted on the topic of sexual violence and its effects on chronic illness and health. Due to the thematic methodology employed, articles were subjected to critical appraisal, with particular emphasis on the study's objectives and findings. Three major themes were concluded from the study: the tendency to develop high-risk behaviors; the occurrence of trauma and stress; and the presence of conditions with somatic and physical symptoms that lead to chronic disease. The themes resulting from this study show a link between sexual violence and its relationship with behavioral and lifestyle changes that ultimately have a physical impact.